Factors Influencing Study Program Choice and Learning Outcomes among Pre-Clinical Students of the Faculty of Medicine, University of Alkhairaat Palu - Ricky Yuliam; Nita Damayani; Nurul Rahma; Sarmila SY. Sakula (Journal of Innovative and Creativity, 2025)
Medical Education plays a crucial role in producing competent healtcare professionals. Both the decision to choose a medical study program and the academic performance of students are influenced by various internal and external factors. The study purpose was to identify factors influencing the choice of the medical study program and the learning outcomes among pre-clinical students at the Faculty of Medicine, Univeristy of Alkhairaat Palu. Materials and methods. A descriptive qualitative approach was employed. Data were collected through in-depth interviews with pre-clinical medical students at University of Alkhairaat Palu. Data were analyzed thematically using ATLAS.ti 25 software. Results. The study revealed that choosing the medical program was driven by personal interest, family encouragement, professional prestige and long-term career goals. Students’ learning outcomes were influenced by internal factors including family support, social environment, and campus facilities. A significant relationship was observed between the initial motivation for choosing medicine and students’ persistence in learning, which affected their academic performance. Conclusions. Both the choice of study program and learning outcomes among pre-clinical medical students are shaped by interconnected personal and environmental factors. Understanding these factors can help educational institutions design more effective strategies for learning support and academic guidance to enhance students success.